Alexis's half-baked idea - Simon, Coco (Simon, Coco. Cupcake diaries, 2019)
When Alexis decides she wants to be more like her popular older sister, Dylan, she tries out for cheerleading, without really thinking about what that entails, including that her sister was a star on her cheerleading squad.